2016
DOI: 10.18632/oncotarget.8456
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to the second-generation androgen receptor antagonist enzalutamide in castration-resistant prostate cancer

Abstract: Enzalutamide (MDV3100) is a second generation Androgen Receptor (AR) antagonist with proven efficacy in the treatment of castration resistant prostate cancer (CRPC). The majority of treated patients, however, develop resistance and disease progression and there is a critical need to identify novel targetable pathways mediating resistance. The purpose of this study was to develop and extensively characterize a series of enzalutamide-resistant prostate cancer cell lines. Four genetically distinct AR-positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 44 publications
14
108
0
Order By: Relevance
“…This might be one of the mechanisms explaining why ENZA was partially effective for ABI‐resistant CRPC patients. In contrast, the AR expression of ENZA‐resistant prostate cancer cell lines did not increase consistently, showing that non‐AR mediated mechanisms are mainly associated with treatment resistance . These mechanisms of resistance to ENZA could not be overcome by ABI.…”
Section: Discussionmentioning
confidence: 83%
“…This might be one of the mechanisms explaining why ENZA was partially effective for ABI‐resistant CRPC patients. In contrast, the AR expression of ENZA‐resistant prostate cancer cell lines did not increase consistently, showing that non‐AR mediated mechanisms are mainly associated with treatment resistance . These mechanisms of resistance to ENZA could not be overcome by ABI.…”
Section: Discussionmentioning
confidence: 83%
“…DU-145, PC-3 and 22RV1 are castration resistant prostate cancer cell lines and LNCaP is castration sensitive prostate cancer cell line which is sensitive to castration [10, 11]. Figure 2 showed that DU-145 and PC-3 has higher expression of PRKAR2B than22RV1 and LNCaP (Figure 2A and 2B).…”
Section: Resultsmentioning
confidence: 99%
“…LNCaP (ATCC, CRL‐1740) and PC‐3 (CRL‐1435) cells were obtained from American Type Culture Collection (ATCC, Manassas, VA). In order to take account of the evolution of prostate cancer during androgen deprivation treatment, an established enzalutamide resistant cell line (LNCaP‐EnzR) was additionally used as a model of advanced CRPC . LNCaP‐EnzR cells were a generous gift from Dr. Donald J. Vander Griend (Urological Stem Cell Research, University of Chicago).…”
Section: Methodsmentioning
confidence: 99%
“…LNCaP‐EnzR cells were a generous gift from Dr. Donald J. Vander Griend (Urological Stem Cell Research, University of Chicago). The cells have been extensively described before . PNT1A epithelial cells were provided by Pirkko Härkönen (Institute of Biomedicine, University of Turku, Turku, Finland) .…”
Section: Methodsmentioning
confidence: 99%